APPLICATIONS IN THE TEXT ON CONVERSION NUMBERS RECEIPT PRINTING USING MICROSOFT VISUAL BASIC 6.0 - Ramdani Ramdani; Jalinas, SKom, MMSI Jalinas, SKom, MMSI (Jurnal Sistem Informasi, 2002)
The use of computer applications is one way or the other alternative in facilitating aprocess of work, especially the printing of receipts. The conversion process numbersin the form of text that is in the printing of receipts, actually very easy to implement iftruly understand the process of printing a receipt. With this application in order tosimplify and accelerate the work relating to the calculation of money so we do notwork over and over again and not waste time there.